Exploring Interactive Learning Environments Based on Augmented Reality Technology - Deng, Weifeng; Wang, Lin; Deng, Xue (International Journal of Interactive Mobile Technologies (iJIM), 2024)
With the rapid advancement of digital technology, the application of augmented reality (AR) in the field of education has emerged as a focal point of research aimed at enhancing learning efficiency and experience through innovative interactive learning environments. This study focuses on the application of AR technology in education. The goal is to address key technical issues present in existing AR interactive learning environments to promote their widespread adoption in educational settings. An analysis of the current application of AR technology in education is conducted, focusing on its potential to enhance learners’ motivation and comprehension capabilities. However, a common shortfall in existing research methodologies has been identified, namely inadequate control over node consistency and deficient design of collaborative visualization components. These limitations restrict interaction and collaborative efficiency within AR learning environments. In response, a novel predictive algorithm for node consistency control is proposed, significantly enhancing real-time interaction and coherence among multiple learners through optimized information synchronization mechanisms. Furthermore, a set of collaborative visualization components is designed to be personalized according to learners’ behavioral and cognitive characteristics, thereby supporting more effective team-based learning. The outcomes of this study not only provide new theoretical and technical support for the design and implementation of AR interactive learning environments but also offer a fresh perspective on the future direction of educational technology.